2020
DOI: 10.1039/d0sc02712j
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature-boosted high efficiency photo-induced charge transfer for remarkable SERS activity of ZnO nanosheets

Abstract: Improving photo-induced charge transfer (PICT) efficiency is the key factor for boosting surface-enhanced Raman scattering (SERS) performance of semiconductor nanomaterials. Introducing plentiful surface defect states in porous ZnO nanosheets (d-ZnO...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…39 ZnO is a high refractive index semiconductor material and shows obvious merits as a SERS substrate. [40][41][42] Wen et al observed the SERS effect of pure ZnO colloids using a cyanine dye D266 as probe molecules in 1996. 43 Researchers have designed and fabricated ZnO nanostructure with various morphologies to realize enhanced SERS activity.…”
Section: Semiconductor Sers Substratesmentioning
confidence: 99%
“…39 ZnO is a high refractive index semiconductor material and shows obvious merits as a SERS substrate. [40][41][42] Wen et al observed the SERS effect of pure ZnO colloids using a cyanine dye D266 as probe molecules in 1996. 43 Researchers have designed and fabricated ZnO nanostructure with various morphologies to realize enhanced SERS activity.…”
Section: Semiconductor Sers Substratesmentioning
confidence: 99%
“…4c), which is likely due to the charge transfer (CT) effect. [60][61][62][63][64] Laser annealing at 5.5 mW with different irradiation times was also performed (Fig. 4f ), which shows the highest SERS signals from the Au@c-TiO 2 with a 30 s laser annealing, followed by a linear decay over time.…”
Section: Surface Enhanced Raman Scattering (Sers) Via Hot Electron Tr...mentioning
confidence: 99%
“…However, novel semiconductors need to be further explored for superior sensitivity. Enhancement of charge transfer (quantum yield) on semiconductors for single-molecule level SERS has drawn considerable attention via further (1) improvement of the photoinduced charge generation [30] and (2) strengthening of the interaction between sites and probe biomolecules [17,[31][32][33]. Furthermore, along these two lines, the understanding of SERS enhancement mechanism could be greatly deepened and enriched.…”
Section: Introductionmentioning
confidence: 99%